Bond stress-slip relationship of oil palm shell lightweight concrete - Mo, Kim Hung; Visintin, P.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin (Elsevier, 2016)
This paper presents the investigation on the local bond stress-slip behaviour of lightweight oil palm shell concrete (OPSC). The bond properties of the OPSC specimen with varying reinforcing bar diameters (12 and 16 mm), concrete cover sizes (50, 75 and 100 mm) and compressive strengths (25 and 35 MPa) were explored. A concrete cover size to reinforcing bar diameter (C/D) ratio of more than 4.17 resulted in pull-out failure while the ratio of 3.13 caused splitting cracks in the OPSC specimens. The reinforcing bar diameter, concrete cover size and compressive strength affected the normalized bond strength, provided that the splitting failure occurred in the concrete specimens. The proposed bond model for splitting failure incorporating the C/D ratio used in the closed-form solution for prediction of the serviceability crack width was found to give good estimation of the experimental results obtained from the full-scale beam tests.